Budgeting as a Key Component of University Management Success - Feicher, Oksana (Socio-Cultural Management Journal, 2022)
Introduction. In modern conditions of economic processes, the essence of university management does not meet the requirements of a democratic society. This is especially true of financial management methods. The need to implement budgeting in the university sector is exacerbated by the significant interest of managers and stakeholders in the autonomy of educational institutions. Purpose and methods. The purpose of the article is to substantiate the theoretical and methodological provisions for defining the concept of “budget” in the context of universities with further disclosure of its role and importance in ensuring effective management. The methodological basis was the fundamental provisions of modern economic concepts, a systematic approach, general and special methods. Results. The way of formation of the category “budget” for the university sector is investigated. The peculiarities of the transformation of scientific thought regarding the introduction of the budgeting process at the university are determined. The priority sources of filling the budgets of the universities of the leading countries for further implementation in the domestic system are identified. Conclusions. Formed own vision of the concept of “budget”, “budgeting” for the university sector; the universal model of realization of the process of budgeting in university considering features of educational activity is presented; the priority sources of budget financing in modern universities are defined because of their historical, geographical, and national features of formation and development. Dominant among them are state target expenditures, expenditures from local budgets of territorial communities, financial revenues from autonomous activities, and targeted funding of scientific activities by the state and business agents.